Association of Interleukin‐1 beta and tumor necrosis factor‐alpha genetic polymorphisms with gastric cancer in India. (9th August 2018) - Sultana, Zareen; Bankura, Biswabandhu; Pattanayak, Arup Kumar; Sengupta, Debmalya; Sengupta, Mainak; Saha, Makhan Lal; Panda, Chinmay Kumar; Das, Madhusudan
Abstract : Interleukin 1 beta ( IL‐1β ) and Tumor necrosis factor alpha ( TNF‐α ) are key inflammatory cytokines whose polymorphisms have been correlated with increased susceptibility to gastric cancer (GC). Since geographical and racial differences exist in cancer rates, our study was aimed to evaluate the first possible association of polymorphisms in these genes with GC risk in West Bengal, India. Polymorphisms in IL‐1β and TNF‐α genes were genotyped in 120 GC patients and 135 healthy individuals. Combined effect of the SNPs in both genes with GC risk was determined through allele dosage analysis (ADA) and the survival data were analyzed by Log Rank Test. The study results revealed that IL‐1β rs1143627: T > C, rs16944: C > T ( p = 0.001;OR = 1.85; 95% CI 1.30‐2.63) and rs1143633: G > A ( p < 0.0001; OR = 2.53; 95% CI 1.67‐3.83) and TNF‐α rs1800630: C > A, rs1799964: T > C ( p < 0.0001; OR = 2.31; 95% CI 1.54‐3.46) polymorphisms significantly contributed toward GC risk. Moreover, ADA showed that carriage of 7 "effective" risk alleles conferred a risk of almost 10‐fold in comparison to individuals carrying less than 3 "effective" risk alleles. Our survival analysis also indicated a significant association between IL‐1β rs1143627: T > C and rs16944: C > T and patient survivability. The presence of H. pylori enhanced the risk in individuals with IL‐1β rs1143627:CC and rs16944:TT genotypes. Further, meta‐analysis revealed significant association of IL‐1β rs1143627: T > C ( p = 0.026; OR = 4.165; 95% CI 1.18‐14.65) and rs16944: C > T ( p = 0.01; OR = 5.49; 95% CI 1.48‐20.37) in presence of H. pylori with gastric cancer in Asian population though no significant difference ( p > 0.05) was found when compared to absence of H. pylori Environ. Mol. Mutagen. 59:653–667, 2018. © 2018 Wiley Periodicals, Inc.